Downstep in Pari the tone system of a western Nilotic language - Torben Andersen (LibraryPress@UF, 1988)
Pari, a Western Nilotic language, has a terraced-level tone system with total downstep. Although Pari could be analyzed as having three basic tone levels and automatic downstep, there is morphological evidence that it has two basic tone levels and non-automatic downstep. Furthermore, there is evidence that downstep is the manifestation of a floating high tone. Floating tones thus behave differently from tones of deleted vowels. In spite of many surface differences between Pari and Luo, a related language, a single tone change accounts for their underlying differences.